Linking community-based programs and service delivery for improving maternal and child nutrition - Tontisirin, Kraisid; Gillespie, Stuart (World Scientific Publishing, 1999)
Generic lessons from past experience with community-based nutrition programming relate more to processes adopted than to specific actions implemented -- more "how" than "what